User Profiling Based on the Identities of Information Sources - Małyszko , Jacek; Węckowski , Dawid (Studia Oeconomica Posnaniensia, 2017)
Along with the increased activity of people on the web, more and more information about them can be gathered based on the analysis of which web pages they visit, what data about themselves they put on the web and who they make contact with. Such information can be used to build so-called virtual identities of web users. Th is article presents the results of research on the problem of building an initial user identity in a situation, when the information about the user is limited very much, i.e. in the early stages of interaction with the system. A solution to this problem is proposed, in which the initial identities are constructed and based on the identity of information sources, which have been declared by the users as relevant to their information needs. Th e conducted experiment revealed that such identities of information sources can be used to build initial user identities.